BIOEKOLOGI DAN KEMAMPUAN MENOCHILUS SEXMACULATUS (COLEOPTERA: COCCINELLIDAE) SEBAGAI PREDATOR KUTU TANAMAN CABAI - , Dahlia Simanjuntak, Ir.,M.Si.; , Prof. Dr. Ir. Fransiscus Xaverius Wagiman, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In-depth research on bioecology and performance of Menochilus sexmaculatus was intended to evaluate the potential of the predator as a biological control agent against pests of sucking insects on chili. Survey of M. sexmaculatus abundance was conducted at central chili production areas, both in lowlands and highlands. The feeding tests of M. sexmaculatus using local chicken egg, quail egg, Corcyra cephalonica egg and Aphis craccivora were done to determine suitable food for mass breeding of the predator. The effectiveness of M. sexmaculatus at controlling aphid was done using sihalotrin 25 EC as a comparator. The research result proved that predatory M. sexmaculatus of imago stadia in low population was found on chilli and nine other types of plant (corn, eggplant, strawberry, long bean, soy bean, mung bean, nut bean, rice and tomato) in highlands and lowlands in Java. Elevation does not affect the abundance of M. exmaculatus. Chili aphids found were B. tabaci of imago stadia in very low population and A. gossypii of all stadia in higher population than that of B. tabaci. The suitable food for mass breeding of M. sexmaculatus is A. craccivora, whereas local chicken egg, quail egg, and C. cephalonica egg-based food egg are not the suitable ones. Predatory M. sexmaculatus is effective in controlling chilli pest aphids including A. gossypii.